Changes of cell structure in ginger during processing - Murad, Noor Azian (Elsevier B.V., 2004)
The purpose of this study was to examine the histological changes of cell structure in ginger during pre-treatment, steaming under pressure and solvent extraction of the oleoresin. The effects of pre-treatment on ginger were studied using fresh ginger, dried ginger, fresh ginger blanched at three different times (5, 10 and 15 min) at atmospheric pressure. Steaming of dried ginger prior to steam distillation was said to hasten the process. The effects of steaming dried ginger with varied durations (30 min, 1 h and 2 h) and under varied pressures (0.3, 0.6 and 0.9 bar gauge) were also studied. Ginger oleoresin was obtained through solvent extraction. The effects of solvent extraction on ginger tissues, dried and fresh were observed after 3 h of extraction. The tissues were stained with Saffranin and Fast Green. The histological analysis was done using a light microscopy (LM) and had revealed some important information about the changes in the cell's structure. Through LM studies, it was confirmed that drying was a vital procedure for pre-treatment to speed up processing time. The reconstruction of parenchyma cell walls was observed after 30 min of steaming, which prolonged the steam distillation time and 3 h of solvent extraction time was insufficient for the extraction of the oleoresin.